Big Constraints to Small Firms’ Growth? Business Environment and Employment Growth across Firms - Aterido, Reyes; Hallward-Driemeier, Mary; Pages, Carmen (2012)
Using data on more than 56,000 enterprises in 90 countries, this paper finds that objective conditions in the business environment vary substantially across firms of different sizes and that there are important non-linearities in their impact on employment growth. The paper focuses on four areas: access to finance, business regulations, corruption, and infrastructure. The results, particularly on the impacts of finance and corruption on growth, depend on whether and how the analysis accounts for the possible endogeneity of the business environment. Controlling for endogeneity revises the finding that small firms benefit most from access to finance, particularly for sources of finance associated with investment and growth. The findings are also sensitive to how small is defined. Differentiating micro (less than 10 employees) from other small firms shows that, while small firms can be disadvantaged in such an environment, micro firms tend to be proportionally less affected by a weak business climate and, on occasion, it can help them to grow. Overall, allowing different size classifications provides insights into the impact of the business environment that are lost in more aggregate analyses.